Relaxation of Imprinting in Trophoblastic Disease - Ariel, I.; Lustig, O.; Oyer, C.E.; Elkin, M.; Gonik, B.; Rachmilewitz, J.; Biran, H.; Goshen, R.; de Groot, N.; Hochberg, A. (Gynecologic oncology, 1994)
Genomic imprinting—the uniparental-dependent transmittance of a genetic trait—has been accepted in recent years as a major mechanism in mammalian genetics. We studied the expression of the H19 gene, a parentally imprinted (maternally expressed) gene, by in situ hybridization in human placenta and trophoblastic disease. Expression was found to be abundant, in a decreasing order, in the intermediate trophoblast (villous and interstitial), the cytotrophoblast, and the syncytiotrophoblast. The villous stroma was also prominently labeled. Partial hydatidiform mole showed a similar pattern of expression as normal placenta. As expected, complete hydatidiform mole, whose genome consists of two haploid sets of paternal origin, was not labeled in the villous stroma and surrounding trophoblastic layer. However, some of the large mononuclear cells in the proliferating groups sprouting from the villous surface were strongly labeled. Prominent expression of H19 was found in placental site trophoblastic tumor and gestational choriocarcinoma. The phenomenon of emergence of expression of alleles subject to repression according to their gamete of origin is termed relaxation of imprinting, and is considered to be relevant to tumorigenesis. We suggest that the expression of the maternally expressed H19 gene in the androgenetic tissue of complete hydatidiform mole represents relaxation of imprinting and may be associated with its malignant potential.